Production of Human Acid-Alpha Glucosidase With a Paucimannose Structure by Glycoengineered Arabidopsis Cell Culture - Sariyatun, Ratna; Florence,; Kajiura, Hiroyuki; Ohashi, Takao; Misaki, Ryo; Fujiyama, Kazuhito (Frontiers in Plant Science, 2021)
Plant cell cultures have emerged as a promising platform for the production of biopharmaceutics due to their cost-effectiveness, safety, ability to control the cultivation, and secrete products into culture medium. However, the use of this platform is hindered by the generation of plant-specific N-glycans, the inability to produce essential N-glycans for cellular delivery of biopharmaceutics, and low productivity. In this study, an alternative acid-alpha glucosidase (GAA) for enzyme replacement therapy of Pompe disease was produced in a glycoengineered Arabidopsis alg3 cell culture. The N-glycan composition of the GAA consisted of a predominantly paucimannosidic structure, Man3GlcNAc2 (M3), without the plant-specific N-glycans. Supplementing the culture medium with NaCl to a final concentration of 50 mM successfully increased GAA production by 3.8-fold. GAA from an NaCl-supplemented culture showed a similar N-glycan profile, indicating that the NaCl supplementation did not affect N-glycosylation. The results of this study highlight the feasibility of using a glycoengineered plant cell culture to produce recombinant proteins for which M3 or mannose receptor-mediated delivery is desired.